The Evolving Technology-Augmented CourtroomBefore, During, and After the Pandemic - Lederer, Fredric I. (2021)
Even before the COVID-19 Pandemic, technology was changing the nature of America’s courtrooms. Access to case management and e-filing data and documents coupled with electronic display of information and evidence at trial, remote appearances, electronic court records, and assistive technology for those with disabilities defined the technology-augmented trial courtroom. With the advent of the Pandemic and the need for social distancing, numerous courts moved to remote appearances, virtual hearings, and even virtual trials. This Article reviews the nature of technology-augmented courtrooms and discusses virtual hearings and trials at length, reviewing legality, technology, human factors, and public acceptance, and concludes that virtual hearings will continue after the Pandemic